Overview of covid-19 regarding the cardiovascular situation in the light of current reports - Aydin, Suna; Akkoc, Ramazan Fazil; Aydin, Suleyman (Bentham Science Publishers, 2020)
Nowadays Coronavirus Disease 2019 (Covid-19) is increasing mortality all over the world mercilessly. We are learning almost every day about its new symptoms and that it mutates quickly. This disease has tied us up and made us desperate. The death rate from this disease has increased in patients who had pre-existing medical conditions, especially cardiovascular ones, by eliminating the angiotensin-converting enzyme (ACE)-2 receptor in the lungs. Also, ACE1 and angiotensin receptor blockers (ARB) may stimulate ACE2 expression and worse the prognosis. Intravenous infusions of ACEIs and ARBs in experimental animals increase the number of ACE2 receptors. Therefore, it may be one of the reasons that COVID-19 infects the cells of patients treating hypertension. However, most of the congress of cardiology do not recommend to discontinue these anti-hypertensive drugs. Therefore, this brief report evaluates Covid-19 in the view of cardiovascular diseases taking into account current reports and suggests some possible solutions to keep the virus under control. © 2020 Bentham Science Publishers.
Keywords: Angiotensin-converting enzyme (ACE)-2 receptor; Asthma; Cardiovascular diseases; Covid-19; Drug; Pneumonia